Comparative Analysis of Service Quality, Price Perception and Product Quality on Consumer Satisfaction at Indomaret and Alfamart Minimarkets in Indonesia - Yuniarsih, Niar; Ramly, Amir Tengku (Diversity: Jurnal Ilmiah Pascasarjana, 2023)
This study aims to determine differences in consumer satisfaction as the dependent variable (Y) and the independent variable (X) are service quality, price perception, and product quality at Indomaret and Alfamart minimarkets in Indonesia. The population is someone who has bought products at Indomaret and Alfamart throughout Indonesia. This study involved two categories, so that the sample for both categories was 30 respondents. The research data used are primary and secondary data with data collection techniques using an online questionnaire instrument with a google form application and data measurement using a Likert Scale. The data were analyzed by Independent Sample T-Test using SPSS, and the results showed that the variables of service quality (X1), price perception (X2), product quality (X3), and customer satisfaction (Y) at Indomaret and Alfamart are the same or there is no difference, and strengthened by the probability value of all variables is Sig. (2-tailed) > 0.05.Keywords: service quality, price perception, product quality, Indomaret, Alfamart